Nilai Lokalitas Penafsiran Kalimatun sawā` QS Ali Imran Ayat 64 Perspektif Nurcholish Madjid - Abdul Azis Fatkhurrohman (Jurnal test, 2024)
This paper tries to present the other side of Nurcholish Madjid's interpretation of the term kalimatun sawā` in surah Ali Imran [3] ayah 64. The interpretation of the verse, which has tended to be interpreted uniformly in the tafsir tradition, is interpreted differently by Nurcholish Madjid. In addition, behind his interpretation he proposes an offer of locality orientation in a broader context. The aspect of locality that has been the dominant starting point of the interpretation of the Qur'an, for Nurcholish Madjid is used as a point of departure that is sought to strengthen his interpretation. This research belongs to the qualitative research model. By using a library research approach, the author will explore Nurcholish Madjid's argumentation in interpreting Surah Ali Imran verse 64, especially on the term kalimatun sawā`. As a result, the interpretation of the verse shows a legitimization of the view of locality which in this case is interpreted as Pancasila. The term kalimatun sawā` , which is the key word in this verse, leads to the confirmation of the argumentation built with the results of the interpretation carried out. This view is very reasonable because the spirit of the values and messages of the Qur'an that preach the unity of the people does not limit the partition in a broad social context. Although explicitly Nurcholish Madjid's study of the Qur'an does not produce unity in terms of methodology, the spirit that is built cannot be separated from the values of the Qur'an itself.